PEMANFAATAN SCHOOLNET (JARDIKNAS ZONA SEKOLAH) OLEH PELAJAR SMP DI KOTA PALEMBANG - Sa’uda, Siti; Yudiastuti, Helda (JURNAL ILMIAH MATRIK, 2014)
This study aims to analyze the use of Schoolnet by junior high school students in the city of Palembang . The data used are primary data using questionnaires . The method used is descriptive method of quantitative sampling techniques in this study using non- probability sampling technique . The survey was conducted by interview and gave questionnaires to students in junior predetermined . The model used to explain the acceptance of Schoolnet is a model of TAM in determining the number of factors influence their decision about how and when to use the system , particularly in terms of : usefullnes ) and ease of use. Tests carried out using multiple linear regression techniques and performed with SPSS software version 17 . The result is expected to contribute positively to the government especially in the application Pustekkom ICT-based learning in schools.